Sightseeing, social climbing, steamboats and sex: Anne Lister's 1828 tour of Scotland. Issue 4 (2nd October 2018) - McHugh, Kirsty
ABSTRACT: This article uses Anne Lister's diaries as the basis of an exploration of writing about travel as part of a diary-keeping routine. It focuses on entries relating to Lister's tour of Scotland in 1828 to reveal an underexplored period of her life and suggest how diaries can shed new light on the experience of home tour travel in the early nineteenth century. This study, while bringing new information about, and insights into, one of Lister's least explored lesbian relationships, firmly places the author within her historical context and social circle. It argues that the diary form allows Lister to record a broader range of travel experiences, and that the full picture she presents of her inner and outer lives provides insights into her motivations as a traveller that are rare in a conventional tour journal. However, Lister's self-imposed record-keeping rules and quirks make these diaries subjective and idiosyncratic as sources, and an awareness of Anne Lister's diaries as a site of self-fashioning is important when reading them as travelogue.